Remember of Khark Aysaevich Ibragimov - Abdulagatov, Zaid Magomedovic (History, Archeology and Ethnography of the Caucasus, 2013)
This article is an obituary devoted to the life and scientific activity of Khark Aysaevich Ibragimov